Discourses of internet freedom - Jack, Caroline (AoIR Selected Papers of Internet Research, 2013)
Using Edwards’s adaptation of Foucault’s concept of discourse, this paper analyzes discourses of “internet freedom” that articulate notions of autonomy, coercion, the state and the individual in and through information and communication technologies, in order to better understand positive and normative understandings of the allocation of power in the digital age. Following an analysis of press accounts, policy texts and influential digital manifestos, two conclusions emerge in light of historically based understandings of autonomy and political subjectivity. First, internet freedom discourses demonstrate that language around ICTs employs ambiguous and contested notions of both users as political subjects, and of the entities that can limit those subjects’ autonomy. Second, a critical reappraisal of political subjectivity and autonomy in light of digital technology can draw on the intellectual heritage of the twentieth century via a reinterpretation of Berlin’s schema of positive and negative liberties.